PERANCANGAN SISTEM INFORMASI LAYANAN ANGGOTA PADA KOPERASI KARYA BERSAMA MEPI (KKBM) - Muhammad Rafi Alfarizi; Imamulhakim Syahid Putra (Jurnal Riset Teknik Komputer, 2026)
In the digital era, cooperatives are required to improve the efficiency and accuracy of managing member service data, particularly savings and loan transactions. Koperasi Karya Bersama Mepi (KKBM) still relies on semi-manual recording using ledgers and spreadsheets, which poses risks such as data entry errors, inconsistencies, and difficulties in retrieving historical data. This study aims to design an integrated Member Service Information System to enhance data management efficiency and accuracy. The method used is User-Centered Design (UCD), which emphasizes user involvement throughout the development process, including understanding the context of use, specifying user requirements, designing solutions, and conducting evaluations. The results show that the designed system simplifies the management of member data, savings, and loan transactions in a structured manner. Features such as integrated data input, transaction history, and automated report generation significantly improve work efficiency and reduce errors. Additionally, the user-friendly interface enhances the overall user experience for administrators. Based on usability evaluation, the system effectively meets user needs and improves cooperative operational performance. Therefore, the implementation of a UCD-based information system is an appropriate solution to support the digital transformation of cooperative services.